Labor market reforms and unemployment dynamics - Fabrice Murtin; Jean-Marc Robin (Centre for Microdata Methods and Practice (cemmap), 2014)
In this paper, we quantify the contribution of labor market reforms to unemployment dynamics in nine OECD countries (Australia, France, Germany, Japan, Portugal, Spain, Sweden, the United Kingdom and the United States). We build and estimate a dynamic stochastic search-matching model with heterogeneous workers, where aggregate shocks to productivity fuel up the cycle, and unanticipated policy interventions shift structural parameters and displace the long-term equilibrium. We show that the heterogeneous-worker mechanism proposed by Robin (2011) to explain unemployment volatility by productivity shocks works well in all countries. The amount of resources injected into placement and employment services, the reduction of UI benefits and product market deregulation stand out as the most prominent policy levers for unemployment reduction. All other LMPs have a significant but lesser impact. We also find that business cycle shocks and LMPs explain about the same share of unemployment volatility (except for Japan, Portugal and the US).
Keywords: E24; E32; J21; 330; Unemployment dynamics; turnover; labor market institutions; job search; matching function